2023
DOI: 10.1101/2023.03.10.532054
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Boosting sleep slow waves suppresses dreaming

Abstract: Previous findings suggest a negative correlation between slow oscillations (SO) in posterior brain regions and dreaming. Here we use a precise closed-loop auditory stimulation (CLAS) procedure to causally test whether slow oscillations suppress dreaming. Our results show that boosting posterior SO during NREM sleep decreases the likelihood of dreaming as compared to no SO boosting. This study provides the first causal evidence for the neural correlates of dreaming.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…CLAS has recently shown applications in enhancing theta wave (3-7 Hz) activity within REM sleep (Harrington et al, 2020), resulting in extended suppression of theta wave after a short boost and prolonged beta power enhancement. This possibility of CLAS to manipulate theta oscillatory activity during REM sleep, might extend recent advances in the use of CLAS during NREM sleep to modulate dream experiences (Juan et al, 2023), paving the way for new, physiology-focused nightmare therapies.…”
Section: Conclusion Limitations and Future Outlookmentioning
confidence: 90%
See 2 more Smart Citations
“…CLAS has recently shown applications in enhancing theta wave (3-7 Hz) activity within REM sleep (Harrington et al, 2020), resulting in extended suppression of theta wave after a short boost and prolonged beta power enhancement. This possibility of CLAS to manipulate theta oscillatory activity during REM sleep, might extend recent advances in the use of CLAS during NREM sleep to modulate dream experiences (Juan et al, 2023), paving the way for new, physiology-focused nightmare therapies.…”
Section: Conclusion Limitations and Future Outlookmentioning
confidence: 90%
“…Altogether, while these initial studies exploring CLAS as a non-invasive therapeutic method have modest clinical outcomes, they highlight the usability of the technique in populations with disturbed sleep, and illuminate how CLAS as a form of therapy might present a new and safe way to improve deep sleep (Talamini & Juan, 2020). A recent study indeed demonstrated that using CLAS to boost posterior SO during NREM sleep decreased the likelihood of dreaming, thus opening the possibility to suppress nightmares in clinical populations (Juan et al, 2023).…”
Section: Clinical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation